Optimalisasi Literasi Antibiotik melalui Leaflet Infografis di Era Digital pada Kelompok Ibu Rumah Tangga di Desa Karangsari - Ikhwan Kusuma; Afriza Pujiati; Septi Nurkhasanah; Khaniva Khalilia Alazhar; Dhiya Zulayta (Kolaborasi: Jurnal Pengabdian Masyarakat, 2025)
Introduction: Irrational antibiotic use remains a global public health problem that contributes to the increasing incidence of Antimicrobial Resistance. Low public literacy regarding rational antibiotic use can increase the risk of antibiotic resistance, particularly among housewives who play an important role in family health decision-making. Therefore, effective educational media are needed to improve public understanding regarding proper antibiotic use. Objective: The purpose of this community service was to improve antibiotic literacy among housewives in Karangsari Village through infographic leaflet-based health education and to evaluate the effect of the educational intervention on antibiotic literacy improvement. Method: This public service was conducted using a pre-experimental design with a one group pre-test and post-test approach in April 2026 in Karangsari Village, Purwokerto. Participants consisted of 42 housewives selected using purposive sampling. Educational intervention was carried out through counseling sessions and interactive discussions using infographic leaflets containing information regarding rational antibiotic use, proper antibiotic consumption, and the risks of antibiotic resistance. Antibiotic literacy was measured using pre-test and post-test questionnaires. Data were analyzed using IBM SPSS Statistics version 25 and evaluated using the Paired Sample t-test. Result: The average antibiotic literacy score increased from 58.21 ± 10.34 during the pre-test to 84.12 ± 8.27 during the post-test, with a mean difference of 25.91. Statistical analysis showed a significant difference between pre-test and post-test scores (p-value <0.001). Conclusion: Infographic leaflet-based education effectively improved antibiotic literacy among housewives in Karangsari Village and may serve as an effective community-based strategy to promote rational antibiotic use and prevent antimicrobial resistance.